Protest! . pismo NSZZ "Solidarność", no. 21, 1981 - [Ryszard Helak duty ed., graphic design by Gerard Lewandowski] (NSZZ "Solidarność", 1981)
Creation and circulation: For internal use; After introduction of the Martial Law publication suspended. The edition republished in 1982 treated as a separate title